High sensitive nanocrystal titanium nitride EG-FET pH sensor - Rayanasukha, Yossawat; Porntheeraphat, Supanit; Bunjongpru, Win; Khemasiri, Narathon; Pankiew, Apirak; Jeamsaksiri, Wutthinan; Srisuwan, Awirut; Chaisriratanakul, Woraphan; Hruanun, Charndet; Poyai, Amporn; Nukeaw, Jiti (My University, 2013)
Solid state pH-sensor device with high efficiency has successfully prepared by using TiN thin film as sensing membrane of extended gate field effect transistor (EG-FET) device. This research has described the physical properties and sensing characteristics of TiN membrane thin film which deposited on SiO2/Si substrate through reactive D.C. magnetron sputtering system. Thenanocrytal-TiNwith anatasestructure depended on substrate heating conditions was revealed from glancing angle x-ray diffraction. The IDS-VGS measurement in the standard buffer solutions showed that the sensitivity of fabricated TiN-EGFET pH deviceis 59.82mV/pH. © (2013) Trans Tech Publications, Switzerland.
Keywords: EG-FET; Ion-sensitive; Nanocrystal; pH sensing; Sputtering; Titanium nitride